Pengaruh Akuntabilitas, Kompleksitas Tugas Terhadap Kualitas Audit - Eka Sariningsih (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2013)
In this research, the audit quality was dependent v ariable, and two independent variables were accountability, complexity task and aims to t est empirically the influence of accountability, complexity task, against audit quality. The primary data were taken and applied. Partial Least Square (PLS) model was applied to the data by empowering S martPLS 2.0 M3 Software. The factor analysis was employed by Explanatory Factor Analysis (EFA) o f the SPSS Software. The results showed that the accountability significantly different against audit quality, with positive sign. Therefore, the accountability within inner body of an auditor woul d be significantly different against the audit qual ity produced by the auditors. The complexity task was a lso significantly different against audit quality with the negative sign. Therefore, it indicated tha t the more complexity task the more complicated results of its audit quality. To obtain a general conclusion it was required to broad the scope of t he research. Further research was suggested to focus o n others variables which were not included in this research . . Keywords: accountability, complexity task, audit quality